Agricultural development: an International perspective - HAYAMI, Yujiro (The John Hopkins University Press, 1971)
Introduction; Problems and theory; Agriculture in economic development theories; Theories of agricultural development; Toward a theory of technical and institutional change; International comparisons; International comparisons of agricultural productivity; Sources of agricultural productivity differences among countries; Agricultural growth in the United States and Japan; Resource constraints and technical change; Science and progress in agriculture; Can growth be trasferred?; International transfer of agricultural technology; Technology transfer and land infrastructure; Retrospect and prospect; Growth and equity in agricultural development; Disequilibrium in world agriculture; Agricultural transformation and economic growth; Appendixes.